Identifikasi Produk Unggulan Subsektor Tanaman Perkebunan Setiap Kecamatan di Kabupaten Jombang - Masdukizen Masdukizen; Nerisa Agnesia Widiyanto; Mis Suhartini (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
This study aims to determine the sub-sector of annual plantation crops which are the superior products of each sub-district in Jombang Regency. This research was conducted from June to August 2020. The data collection method in this study used descriptive quantitative. Secondary data were taken from related sources and calculated using location quotient (LQ) analysis. The results of the LQ analysis of land area and production of each sub-district are described and identified to determine the influencing values. The annual plantation products in Jombang Regency during the period 2014-2018 are clove, cocoa, coconut, and coffee plants. The sub-districts that have a production base value and clove plantation area are Together and Wonosalam Districts. For cocoa plants, the sub-districts that have a production base value and cocoa land area are Bareng and Wonosalam sub-districts. For coconuts, the sub-districts that have a coconut production base value are Bandar Kedung Mulyo, Mojowarno, Wonosalam, Sumobito, Peterongan, Jombang, Megaluh, Tembelang, Kesamben, Ploso, Kabuh, and Plandaan sub-districts. Mulyo, Mojowarno, Wonosalam, Sumobito, Peterongan, Jombang, Megaluh, Tembelang, Ploso, and Plandaan. For coffee plants, the sub-district that has a coffee production base value is the Bareng sub-district and Wonosalam for the sub-district which has a coffee base area is the Wonosalam sub-district.